Magnetic molecularly imprinted water purification material capable of being magnetically separated and recovered and preparation method thereof

By chemically bonding disulfide bonds to reversibly crosslink molecularly imprinted polymers on a porous matrix, the problems of specific surface area and magnetic separation efficiency of magnetic molecularly imprinted materials have been solved, enabling efficient water purification and multiple recycling of materials.

CN123038795APending Publication Date: 2026-11-06HEYE HEALTH TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611294800.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-11-06

AI Technical Summary

Technical Problem

Existing magnetic molecular imprinted materials suffer from problems such as limited specific surface area, low magnetic separation and recovery efficiency, difficulty in regeneration, and limited number of recycling cycles. In particular, when loaded onto macroscopic carriers, they face the contradiction of unstable binding and weakened magnetic response.

Method used

Magnetic nanoparticles are dispersed in a one-dimensional fibrous or two-dimensional aerogel porous matrix and rapidly separated and gently regenerated by chemically bonding a molecularly imprinted polymer shell with a reversible cross-linked structure containing disulfide bonds, combined with an external magnetic field.

Benefits of technology

It significantly improves the specific surface area and adsorption capacity, enhances magnetic separation and recovery efficiency, and ensures the stability of the material's recognition performance during long-term use and the retention of its adsorption performance after multiple cycles.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application belongs to the technical field of environmental purification materials, and particularly relates to a magnetic molecular imprinting water purification material capable of magnetic separation and recovery and a preparation method thereof. The material comprises a one-dimensional fibrous or two-dimensional aerogel porous matrix, magnetic nanoparticles are dispersed in the matrix, and a molecular imprinting polymer shell layer with a disulfide bond reversible cross-linking structure is bonded to the surface of the matrix. The molecular imprinting polymer shell layer can break the disulfide bond under the action of a reducing agent, release the recognized template molecules, and re-form the disulfide bond under oxidation conditions to restore the molecular imprinting cavities. The material has high specific surface area, fast magnetic separation response and excellent cyclic regeneration performance, can effectively remove organic pollutants in water bodies, and has good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of environmental purification materials technology, specifically relating to a magnetically separable and recyclable magnetic molecularly imprinted water purification material and its preparation method. Background Technology

[0002] Magnetic molecularly imprinted materials have attracted widespread attention in the field of aquatic organic pollutant treatment in recent years due to their combination of magnetic responsiveness and molecular recognition selectivity. These materials typically use magnetic nanoparticles such as iron oxide (Fe3O4) as a core, coated with a polymer shell containing specific template molecularly imprinted vacancies, thereby achieving efficient capture and rapid magnetic separation and recovery of target pollutants. However, existing magnetic molecularly imprinted materials still face several technical bottlenecks in practical applications.

[0003] Currently, most common magnetic molecularly imprinted materials are in the form of zero-dimensional powders, such as those formed directly on the surface of magnetic particles through suspension polymerization or precipitation polymerization. While the preparation process for these powdered materials is relatively mature, their specific surface area is often insufficient due to the geometric characteristics of the particles themselves, making it difficult to further improve the adsorption capacity per unit mass. A more prominent problem is that these powdered materials are prone to agglomeration during water treatment, which not only weakens the response speed during magnetic separation but also causes some fine particles to be lost with the water flow during separation, reducing the material's recovery rate and reusability. Although researchers have attempted to alleviate these phenomena by controlling particle size distribution or introducing dispersants, the effects are unstable, and the added components may interfere with the recognition accuracy of the imprinted sites.

[0004] To address the inherent limitations of powder morphology, some studies have explored loading molecularly imprinted materials onto macroscopic supports, such as electrospun fiber membranes or three-dimensional porous frameworks. These supports offer larger specific surface areas and more regular channel structures, facilitating mass transfer and contact of target molecules. However, most existing loading strategies rely on physical doping or simple embedding, resulting in insufficient bonding strength between the molecularly imprinted polymer and the support. This leads to easy detachment of the imprinted layer during use, causing a rapid decline in recognition performance. Furthermore, the introduction of the support often shields the surface of some magnetic particles, reducing overall magnetic response sensitivity and prolonging separation time. How to firmly anchor the molecularly imprinted layer onto the surface of a high specific surface area support without sacrificing magnetic separation efficiency remains a pressing challenge.

[0005] Another factor limiting the practical application of magnetic molecularly imprinted materials is their regeneration capability. Traditional molecularly imprinted polymers typically employ highly cross-linked rigid networks to maintain the stability of imprinted holes. While this structure ensures high selectivity and binding strength, it makes the elution of template molecules extremely difficult. Conventional solvent extraction or ultrasonic cleaning often requires multiple cycles to remove most of the template molecules, and each elution causes some degree of irreversible damage to the imprinted holes, resulting in a significant decrease in adsorption capacity after several cycles. In recent years, some researchers have proposed using reversible chemical bonds to construct dynamically cross-linked molecularly imprinted networks, such as introducing disulfide bonds, borate ester bonds, or imine bonds, to achieve temporary dissociation and recombination of the network under specific stimuli, thereby gently releasing template molecules. This type of reversible cross-linking strategy has been preliminarily verified in non-magnetic molecularly imprinted systems, showing potential for improving regeneration performance. However, research combining these reversible cross-linking mechanisms with magnetic separation functions is still in its early stages. Systematic solutions are lacking regarding how to precisely control the switching behavior of reversible bonds while maintaining magnetic response sensitivity, and how to ensure the fidelity of imprinted holes after multiple cycles.

[0006] In summary, existing magnetic molecular imprinting technologies have significant room for improvement in three aspects: morphology and structure, carrier bonding strength, and regeneration and recycling capabilities. On the one hand, the specific surface area and recovery efficiency of powdered materials limit their large-scale application; on the other hand, fixing molecular imprinted layers to macroscopic carriers presents new challenges such as unstable bonding and weakened magnetic response; and traditional highly cross-linked imprinted networks struggle to balance recognition stability and ease of regeneration. Therefore, developing a magnetic molecular imprinted material that can simultaneously optimize specific surface area, enhance magnetic separation and recovery efficiency, and achieve mild and controllable regeneration is of great significance for promoting the practical application of this technology in the field of water treatment. Summary of the Invention

[0007] This application aims to overcome the shortcomings of existing technologies where magnetic molecular imprinted materials are in the form of zero-dimensional powder, resulting in limited specific surface area, limited magnetic separation and recovery efficiency, difficulty in regeneration, and few cycles. Therefore, it provides a magnetically separable and recyclable magnetic molecular imprinted water purification material and its preparation method to overcome the above-mentioned deficiencies.

[0008] To achieve the above-mentioned objectives, the present invention is implemented through the following technical solution: Firstly, this invention provides a magnetically separable and recyclable magnetic molecularly imprinted water purification material. Including porous matrices in the form of one-dimensional fibrous or two-dimensional aerogel; Magnetic nanoparticles are dispersed in the porous matrix; The porous matrix has a molecularly imprinted polymer shell with a reversible cross-linked structure containing disulfide bonds bonded to its surface. The molecularly imprinted polymer shell can break disulfide bonds under the action of a reducing agent, thereby releasing the identified template molecule, and reforming disulfide bonds under oxidative conditions to restore the molecularly imprinted hole.

[0009] As described in the background section, in the field of magnetic molecular imprinting technology, existing research has long faced a core contradiction: how to maintain molecular recognition accuracy while simultaneously ensuring the macroscopic operability and long-term service stability of the material. Although traditional zero-dimensional powder-based magnetic molecular imprinting materials are easy to prepare, their specific surface area is limited by the geometric scale of the particles themselves, making it difficult to further increase the number of effective recognition sites per unit mass. At the same time, powder-based materials are prone to agglomeration during magnetic separation due to the magnetic dipole interaction between particles, resulting in some fine particles not being effectively captured and being lost with the water flow. This not only reduces the single-use recovery rate but also significantly limits the number of times the material can be reused.

[0010] To address these issues, researchers have attempted to load molecularly imprinted layers onto macroscopic supports such as one-dimensional fiber membranes or three-dimensional porous frameworks, hoping to leverage the structural advantages of these supports to achieve higher specific surface area and better fluid permeability. However, these loading strategies generally face a significant technical hurdle: the bonding between the molecularly imprinted layer and the support is often physical adsorption or simple embedding, resulting in weak adhesion. The imprinted layer is easily detached during water erosion or repeated regeneration, leading to a rapid decline in recognition performance. More critically, the introduction of the support often obscures part of the magnetic particle surface, weakening the overall magnetic response sensitivity. This extends magnetic separation, which could have been completed in seconds, to tens of seconds or even longer, thus partially offsetting the mass transfer advantages provided by the support structure.

[0011] Therefore, the design of magnetic molecularly imprinted materials requires a balance between specific surface area, magnetic response sensitivity, and imprint layer stability. Simply changing the morphology introduces new contradictions, while merely optimizing the chemical structure of the imprint layer cannot overcome the inherent limitations of the powder state.

[0012] Based on this understanding of the systemic problem, this application proposes a solution that integrates morphological design with the chemical structure design of the imprinted layer. The core concept is that the carrier is no longer regarded as a passive supporting framework, nor is the molecular imprinted layer regarded as an independent recognition unit. Instead, the two are chemically bonded to form a functionally synergistic whole.

[0013] Specifically, a one-dimensional fibrous or two-dimensional aerogel-like porous matrix is ​​first selected as the main framework. These matrices possess high specific surface area and interconnected pore networks, providing ample contact interfaces and rapid mass transfer channels for subsequent molecular recognition. Subsequently, magnetic nanoparticles are uniformly dispersed within this porous matrix, forming distributed magnetic response nodes throughout the structure, thus avoiding magnetic signal attenuation caused by carrier encapsulation. The most crucial step involves constructing a molecularly imprinted polymer shell containing a reversibly cross-linked disulfide structure on the surface of the porous matrix through chemical bonding. The disulfide bonds here are not simply cross-linking agents, but rather endow the entire imprinted network with a smart responsive characteristic: under normal use, the disulfide bonds maintain the rigid structure of the imprinted holes, ensuring high selective recognition of target molecules; when the material needs to be regenerated, the application of a reducing agent can cause the disulfide bonds to break, and the entire imprinted network will then relax appropriately, allowing the previously tightly bound template molecules to be gently released, avoiding irreversible damage to the imprinted holes caused by traditional strong elution; after the template molecules are removed, the disulfide bonds reform under oxidative conditions, the imprinted network returns to its original dense state, and the shape and size of the holes are accurately restored.

[0014] The reason this design achieves better-than-expected technical results lies in the deep functional synergy among its three structural elements. First, the high specific surface area of ​​the porous matrix and the distributed magnetic nanoparticles together constitute a highly efficient mass transfer-separation coupling system. Pollutant molecules can fully contact the imprinted sites as they flow through the porous channels, significantly increasing the adsorption rate. Simultaneously, because the magnetic particles are dispersed throughout the matrix rather than concentrated in a localized area, the applied magnetic field exerts a uniform magnetic force on the entire material, allowing the separation process to be completed quickly and significantly improving the recovery rate. Second, a stable interface is formed between the chemically bonded molecularly imprinted shell and the porous matrix, fundamentally eliminating the risk of imprint layer detachment during use and ensuring the stability of the material's recognition performance over long-term operation. Third, and most notably, the synergistic effect lies in the matching relationship between the reversible disulfide cross-linked structure and the open morphology of the porous matrix. In traditional powder systems, even with the introduction of reversible cross-linking, the dense packing of particles restricts the diffusion paths of reducing agents and oxidizing agents, resulting in less than ideal efficiency and uniformity of the reversible reaction. In the porous matrix structure of this application, the interconnected pores provide smooth channels for the penetration of chemical reagents, enabling the breaking and reconstruction of disulfide bonds to occur synchronously and uniformly throughout the material, thus fully leveraging the regenerative advantages of reversible crosslinking. Experimental results show that after multiple adsorption-regeneration cycles, the adsorption capacity of the material remains at a high level, an effect that cannot be achieved by single morphology optimization or single chemical modification.

[0015] In summary, the invention of this application achieves simultaneous improvements in specific surface area, magnetic separation efficiency, and regeneration cycle stability by systematically designing a one-dimensional / two-dimensional porous matrix, distributed magnetic nanoparticles, and a disulfide bond reversibly cross-linked molecularly imprinted shell as an organic whole.

[0016] Preferably, the porous substrate is a one-dimensional electrospun fiber membrane with a thickness of 50-200 μm, a fiber diameter of 200-500 nm, and a porosity of 70%-85%.

[0017] Preferably, the porous matrix is ​​a two-dimensional magnetic aerogel formed by freeze-drying, with a porosity greater than 90% and a density of 0.02–0.05 g / cm³. 3 .

[0018] Preferably, the magnetic nanoparticles have an Fe3O4@PVBC core-shell structure, and the PVBC shell is connected to the RAFT chain transfer agent CPDB.

[0019] Preferably, the molecularly imprinted polymer shell is polymerized from a polymer system comprising a disulfide-bonded monomer, a functional monomer, and a crosslinking agent in the presence of a template molecule.

[0020] Preferably, the disulfide-containing monomer is a bis(2-vinylpyridine) disulfide, and its amount accounts for 3 mol% to 8 mol% of the total monomer.

[0021] Preferably, the reducing agent is dithiothreitol, with a concentration of 5–20 mM, and the treatment time is 20–40 min.

[0022] Secondly, the present invention also provides a method for preparing the aforementioned magnetic molecularly imprinted water purification material, comprising the following steps: (1) Preparation of a porous matrix containing magnetic nanoparticles; (2) Molecular imprinting polymerization is carried out on the surface of the porous matrix, wherein the polymerization system contains reversible crosslinking monomers containing disulfide bonds to form a molecular imprinted polymer shell containing a reversible crosslinking structure of disulfide bonds. (3) Wash away the template molecules to obtain the magnetic molecularly imprinted water purification material.

[0023] Preferably, the porous matrix in step (1) is obtained by electrospinning or freeze-drying.

[0024] Preferably, when electrospinning is used, magnetic nanoparticles are dispersed in the spinning solution and spun into a film.

[0025] Preferably, when freeze-drying is used, magnetic nanoparticles are mixed with chitosan solution and then freeze-dried to form an aerogel.

[0026] Preferably, the molecular imprinting polymerization in step (2) is surface-initiated RAFT polymerization, using CPDB on the surface of magnetic nanoparticles as a chain transfer agent.

[0027] Thirdly, the present invention also provides a method for purifying water using the magnetic molecularly imprinted water purification material. The material is added to water containing organic pollutants, and after the pollutants are adsorbed, the material is separated and recovered by an external magnetic field. Then, a reducing agent is used to break the disulfide bonds in the molecularly imprinted polymer shell, releasing the pollutants. Finally, an oxidation treatment is performed to reform the disulfide bonds, thereby achieving the regeneration and reuse of the material.

[0028] Preferably, the organic pollutant is at least one of bisphenol A, tetracycline, or sulfonamide drugs.

[0029] Therefore, this application has the following beneficial effects: (1) By changing the morphology of magnetic molecular imprinted materials from traditional zero-dimensional powder to one-dimensional fiber membrane or two-dimensional aerogel, the specific surface area is significantly improved, thereby increasing the number of effective recognition sites on a unit mass of material and improving the adsorption capacity for target pollutants. (2) The molecularly imprinted polymer shell is constructed by using a reversible cross-linking structure of disulfide bonds, so that after the material is saturated with adsorption, the template molecules can be gently released by treatment with a reducing agent, and the imprinted holes can be restored by oxidation to rebuild the disulfide bonds. This achieves stable maintenance of adsorption performance after multiple cycles of use and greatly extends the service life of the material. (3) Magnetic nanoparticles are uniformly dispersed in a porous matrix. Combined with the overall structure of fiber membrane or aerogel, solid-liquid separation can be completed quickly under the action of an external magnetic field, significantly improving the recovery efficiency and avoiding the problem of easy loss of powdered materials during the separation process. (4) The molecular imprinted shell is firmly attached to the surface of the porous matrix through chemical bonding, which solves the problem of easy detachment of the imprinted layer in the traditional loading strategy and ensures the structural stability of the material under long-term use and water scouring conditions. Detailed Implementation

[0030] The present invention will be further described below with reference to specific embodiments. Those skilled in the art will be able to implement the present invention based on these descriptions. Furthermore, the embodiments of the present invention described below are generally only some, not all, of the embodiments of the present invention. Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort should fall within the scope of protection of the present invention.

[0031] Example 1 This embodiment provides a method for preparing a magnetically separable and recyclable magnetic molecularly imprinted water purification material, which includes the following steps: Step 1: Preparation of Fe3O4 nanoparticles 2.70 g of ferric chloride hexahydrate (FeCl3·6H2O, analytical grade) was weighed and dissolved in 80 mL of ethylene glycol. The solution was magnetically stirred for 30 min until completely dissolved. 7.20 g of anhydrous sodium acetate and 2.00 g of polyethylene glycol (PEG-4000) were added, and stirring was continued for another 30 min. The mixture was transferred to a 100 mL stainless steel autoclave lined with polytetrafluoroethylene (PTFE), sealed, and placed in an oven at 200 °C for 12 h. After the reaction, the mixture was allowed to cool naturally to room temperature. The black product was collected using a magnet and washed three times each with deionized water and anhydrous ethanol. The product was then vacuum dried at 60 °C for 12 h to obtain Fe3O4 nanoparticles with an average particle size of approximately 200 nm.

[0032] Step 2: Preparation of Fe3O4@PVBC core-shell particles 0.50 g of the above Fe3O4 nanoparticles were dispersed in 50 mL of acetonitrile and ultrasonically dispersed for 15 min. 0.75 g of 4-vinylbenzyl chloride (VBC, 97% purity) and 0.015 g of azobisisobutyronitrile (AIBN, recrystallized and purified) were added, and nitrogen gas was purged for 30 min to remove oxygen. The temperature was raised to 70 °C, and the reaction was magnetically stirred for 8 h under nitrogen protection. After the reaction was completed, the product was magnetically separated, washed three times with acetonitrile, and vacuum dried at 60 °C for 8 h to obtain Fe3O4@PVBC core-shell particles.

[0033] Step 3: Preparation of Fe3O4@PVBC-CPDB magnetic RAFT reagent 0.30 g of the above Fe3O4@PVBC core-shell particles were dispersed in 15 mL of anhydrous tetrahydrofuran. Separately, 0.18 g of 4-cyano-4-[(dodecylthioalkylthiocarbonyl)thioalkyl]valeric acid (CPDB, 98% purity) was dissolved in 5 mL of anhydrous tetrahydrofuran, and 0.03 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC·HCl) and 0.018 g of 4-dimethylaminopyridine (DMAP) were added. The mixture was activated in an ice bath for 30 min. The activated CPDB solution was slowly added dropwise to the Fe3O4@PVBC dispersion, and the reaction was stirred at 25 °C for 24 h. After the reaction, the product was collected by magnetic separation, washed three times each with tetrahydrofuran and anhydrous ethanol, and dried under vacuum at 40 °C for 6 h to obtain the Fe3O4@PVBC-CPDB magnetic RAFT reagent.

[0034] Step 4: Preparation of electrospinning solution 0.45 g of the above Fe3O4@PVBC-CPDB magnetic RAFT reagent was dispersed in 10 mL of N,N-dimethylformamide (DMF) and ultrasonically dispersed for 20 min. 1.55 g of polyacrylonitrile (PAN, Mw=150,000) was added, and the mixture was magnetically stirred in a 60 ℃ water bath for 4 h until completely dissolved to obtain a homogeneous spinning solution.

[0035] Step 5: Electrospinning to prepare magnetic nanofiber membranes The above spinning solution was transferred to a 10 mL syringe equipped with a No. 21 stainless steel flat-tipped needle. An electrospinning apparatus was used, with a receiving distance of 15 cm, an applied voltage of 18 kV, and a feed rate of 0.8 mL / h. Using aluminum foil as the receiving substrate, at an ambient temperature of 25 ℃ and a relative humidity of 45%, spinning was carried out for 4 h to obtain a Fe3O4@PVBC-CPDB / PAN magnetic nanofiber membrane with a thickness of approximately 120 μm and a fiber diameter of approximately 350 nm.

[0036] Step 6: Surface molecular imprinting polymerization 0.20 g of the above magnetic nanofiber membrane was immersed in 20 mL of acetonitrile. 0.050 g of bisphenol A (BPA, template molecule), 0.086 g of 4-vinylpyridine (4-VP, functional monomer), 0.023 g of bis(2-vinylpyridine) disulfide (containing disulfide bonds, accounting for 3 mol% of the total monomers), 0.206 g of ethylene glycol dimethacrylate (EGDMA, crosslinking agent), and 0.005 g of AIBN were added. Nitrogen gas was purged for 30 min to remove oxygen. After sealing, the membrane was placed in a 60 ℃ oil bath and magnetically stirred for 12 h. After the reaction, the fiber membrane was removed and Soxhlet extracted with a methanol / acetic acid (9:1 volume ratio) solution for 24 h to remove the template molecule. It was then washed with methanol until neutral and dried under vacuum at 40 ℃ for 6 h to obtain the Fe3O4@PVBC-CPDB / PAN@MIP magnetic molecularly imprinted nanofiber membrane.

[0037] Example 2 This embodiment provides a method for preparing a magnetically separable and recyclable magnetic molecularly imprinted water purification material, which includes the following steps: Step 1: Preparation of Fe3O4 nanoparticles Same as step 1 in Example 1.

[0038] Step 2: Preparation of Fe3O4@PVBC core-shell particles Same as step 2 in Example 1.

[0039] Step 3: Preparation of Fe3O4@PVBC-CPDB magnetic RAFT reagent Same as step 3 in Example 1.

[0040] Step 4: Preparation of electrospinning solution Disperse 0.35 g of Fe3O4@PVBC-CPDB magnetic RAFT reagent in 10 mL of DMF and sonicate for 20 min. Add 1.65 g of PAN (Mw=150,000) and stir magnetically in a 60 ℃ water bath for 4 h until completely dissolved to obtain a homogeneous spinning solution.

[0041] Step 5: Electrospinning to prepare magnetic nanofiber membranes Same as step 5 of Example 1, adjust the spinning time to 3 h to obtain a magnetic nanofiber membrane with a thickness of about 95 μm and a fiber diameter of about 300 nm.

[0042] Step 6: Surface molecular imprinting polymerization 0.20 g of the above magnetic nanofiber membrane was immersed in 20 mL of acetonitrile. 0.060 g of tetracycline (TC, template molecule), 0.105 g of methacrylic acid (MAA, functional monomer), 0.062 g of bis(2-vinylpyridine) disulfide (containing disulfide bonds, accounting for 8 mol% of the total monomers), 0.198 g of EGDMA, and 0.006 g of AIBN were added. Nitrogen gas was purged for 30 min to remove oxygen. The membrane was then sealed and placed in a 60 ℃ oil bath with magnetic stirring for 14 h. After the reaction, the fiber membrane was removed and Soxhlet extracted with a methanol / acetic acid (9:1 volume ratio) solution for 24 h to remove the template molecule. It was then washed with methanol until neutral and dried under vacuum at 40 ℃ for 6 h to obtain the Fe3O4@PVBC-CPDB / PAN@MIP magnetic molecularly imprinted nanofiber membrane.

[0043] Example 3 This embodiment provides a method for preparing a magnetically separable and recyclable magnetic molecularly imprinted water purification material, which includes the following steps: Step 1: Preparation of Fe3O4 nanoparticles Same as step 1 in Example 1.

[0044] Step 2: Preparation of Fe3O4@PVBC core-shell particles Same as step 2 in Example 1.

[0045] Step 3: Preparation of Fe3O4@PVBC-CPDB magnetic RAFT reagent Same as step 3 in Example 1.

[0046] Step 4: Preparation of magnetic chitosan solution Disperse 0.30 g of Fe3O4@PVBC-CPDB magnetic RAFT reagent in 15 mL of deionized water and sonicate for 15 min. Add 0.60 g of chitosan (degree of deacetylation ≥95%, viscosity 200 mPa·s) and 0.36 mL of glacial acetic acid, and stir magnetically at room temperature for 2 h until the chitosan is completely dissolved to obtain a homogeneous magnetic chitosan solution.

[0047] Step 5: Freeze-drying to prepare magnetic aerogel The above magnetic chitosan solution was transferred to a 3 cm diameter petri dish and pre-frozen at -20 ℃ for 12 h. The frozen sample was then placed in a freeze dryer and freeze-dried at -50 ℃ and a vacuum of less than 10 Pa for 48 h to obtain Fe3O4@PVBC-CPDB / chitosan magnetic aerogel with a porosity of approximately 93% and a density of approximately 0.035 g / cm³.

[0048] Step 6: Surface molecular imprinting polymerization 0.15 g of the above magnetic aerogel was immersed in 20 mL of acetonitrile. 0.045 g of sulfadiazine (SDZ, template molecule), 0.092 g of 4-VP (functional monomer), 0.041 g of bis(2-vinylpyridine) disulfide (monomer containing disulfide bonds, accounting for 5.5 mol% of the total monomers), 0.215 g of EGDMA, and 0.005 g of AIBN were added. Nitrogen gas was purged for 30 min to remove oxygen. After sealing, the aerogel was placed in a 60 ℃ oil bath and magnetically stirred for 12 h. After the reaction, the aerogel was removed and Soxhlet extracted with a methanol / acetic acid (9:1 volume ratio) solution for 24 h to remove the template molecule. It was then washed with methanol until neutral and dried under vacuum at 40 ℃ for 6 h to obtain Fe3O4@PVBC-CPDB / chitosan@MIP magnetic molecularly imprinted aerogel.

[0049] Example 4 This embodiment provides a method for preparing a magnetically separable and recyclable magnetic molecularly imprinted water purification material, which includes the following steps: Step 1: Preparation of Fe3O4 nanoparticles Same as step 1 in Example 1.

[0050] Step 2: Preparation of Fe3O4@PVBC core-shell particles Same as step 2 in Example 1.

[0051] Step 3: Preparation of Fe3O4@PVBC-CPDB magnetic RAFT reagent Same as step 3 in Example 1.

[0052] Step 4: Preparation of electrospinning solution 0.40 g of Fe3O4@PVBC-CPDB magnetic RAFT reagent was dispersed in a mixed solvent of 8 mL DMF and 2 mL acetone and ultrasonically dispersed for 20 min. 1.60 g of polyvinylidene fluoride (PVDF, Mw=275,000) was added and magnetically stirred in a 50 ℃ water bath for 5 h until completely dissolved to obtain a homogeneous spinning solution.

[0053] Step 5: Electrospinning to prepare magnetic nanofiber membranes Following the same procedure as in step 5 of Example 1, the spinning time was adjusted to 3.5 h to obtain a magnetic nanofiber membrane with a thickness of approximately 110 μm and a fiber diameter of approximately 380 nm.

[0054] Step 6: Surface molecular imprinting polymerization 0.20 g of the above magnetic nanofiber membrane was immersed in 20 mL of acetonitrile. 0.055 g of bisphenol A (BPA, template molecule), 0.090 g of 4-VP (functional monomer), 0.025 g of bis(2-vinylpyridine) disulfide (monomer containing disulfide bonds, accounting for 3 mol% of the total monomers), 0.210 g of EGDMA, and 0.005 g of AIBN were added. Nitrogen gas was purged for 30 min to remove oxygen. The membrane was then sealed and placed in a 60 ℃ oil bath with magnetic stirring for 12 h. After the reaction, the fiber membrane was removed and Soxhlet extracted with a methanol / acetic acid (9:1 volume ratio) solution for 24 h to remove the template molecule. It was then washed with methanol until neutral and dried under vacuum at 40 ℃ for 6 h to obtain the Fe3O4@PVBC-CPDB / PVDF@MIP magnetic molecularly imprinted nanofiber membrane.

[0055] Step 7: Reduction and Regeneration Process Take 0.10 g of the above fiber membrane and immerse it in 20 mL of a 5 mM dithiothreitol (DTT) aqueous solution. Shake at 25°C for 40 min. After removal, wash three times with deionized water and then oxidize in air for 12 h to allow the disulfide bonds to reform, completing one regeneration cycle.

[0056] Example 5 This embodiment provides a method for preparing a magnetically separable and recyclable magnetic molecularly imprinted water purification material, which includes the following steps: Step 1: Preparation of Fe3O4 nanoparticles Same as step 1 in Example 1.

[0057] Step 2: Preparation of Fe3O4@PVBC core-shell particles Same as step 2 in Example 1.

[0058] Step 3: Preparation of Fe3O4@PVBC-CPDB magnetic RAFT reagent Same as step 3 in Example 1.

[0059] Step 4: Preparation of electrospinning solution Disperse 0.50 g of Fe3O4@PVBC-CPDB magnetic RAFT reagent in 10 mL of DMF and sonicate for 20 min. Add 1.50 g of PAN (Mw=150,000) and stir magnetically in a 60 ℃ water bath for 4 h until completely dissolved to obtain a homogeneous spinning solution.

[0060] Step 5: Electrospinning to prepare magnetic nanofiber membranes Following the same procedure as in step 5 of Example 1, the spinning time was adjusted to 5 h to obtain a magnetic nanofiber membrane with a thickness of approximately 160 μm and a fiber diameter of approximately 420 nm.

[0061] Step 6: Surface molecular imprinting polymerization 0.20 g of the above magnetic nanofiber membrane was immersed in 20 mL of acetonitrile. 0.070 g tetracycline (TC, template molecule), 0.112 g MAA (functional monomer), 0.065 g bis(2-vinylpyridine) disulfide (monomer containing disulfide bonds, accounting for 8 mol% of the total monomers), 0.195 g EGDMA, and 0.006 g AIBN were added. Nitrogen gas was purged for 30 min to remove oxygen. The membrane was then sealed and placed in a 60 ℃ oil bath with magnetic stirring for 14 h. After the reaction, the fiber membrane was removed and Soxhlet extracted with a methanol / acetic acid (9:1 volume ratio) solution for 24 h to remove the template molecule. It was then washed with methanol until neutral and dried under vacuum at 40 ℃ for 6 h to obtain the Fe3O4@PVBC-CPDB / PAN@MIP magnetic molecularly imprinted nanofiber membrane.

[0062] Step 7: Reduction and Regeneration Process Take 0.10 g of the above fiber membrane and immerse it in 20 mL of 20 mM DTT aqueous solution. Shake at 25 °C for 20 min. After removal, wash it three times with deionized water and then place it in air for oxidization for 12 h to allow disulfide bonds to reform, completing one regeneration cycle.

[0063] Example 6 This embodiment provides a method for preparing a magnetically separable and recyclable magnetic molecularly imprinted water purification material, which includes the following steps: Step 1: Preparation of Fe3O4 nanoparticles Same as step 1 in Example 1.

[0064] Step 2: Preparation of Fe3O4@PVBC core-shell particles Same as step 2 in Example 1.

[0065] Step 3: Preparation of Fe3O4@PVBC-CPDB magnetic RAFT reagent Same as step 3 in Example 1.

[0066] Step 4: Preparation of magnetic chitosan solution Disperse 0.28 g of Fe3O4@PVBC-CPDB magnetic RAFT reagent in 15 mL of deionized water and sonicate for 15 min. Add 0.62 g of chitosan (degree of deacetylation ≥95%, viscosity 200 mPa·s) and 0.38 mL of glacial acetic acid, and stir magnetically at room temperature for 2 h until the chitosan is completely dissolved to obtain a homogeneous magnetic chitosan solution.

[0067] Step 5: Freeze-drying to prepare magnetic aerogel Following step 5 of Example 3, Fe3O4@PVBC-CPDB / chitosan magnetic aerogel was obtained, with a porosity of approximately 92% and a density of approximately 0.038 g / cm³. 3 .

[0068] Step 6: Surface molecular imprinting polymerization 0.15 g of the above magnetic aerogel was immersed in 20 mL of acetonitrile. 0.048 g of sulfadiazine (SDZ, template molecule), 0.095 g of 4-VP (functional monomer), 0.043 g of bis(2-vinylpyridine) disulfide (monomer containing disulfide bonds, accounting for 5.5 mol% of the total monomers), 0.218 g of EGDMA, and 0.005 g of AIBN were added. Nitrogen gas was purged for 30 min to remove oxygen. After sealing, the aerogel was placed in a 60 ℃ oil bath and magnetically stirred for 12 h. After the reaction, the aerogel was removed and Soxhlet extracted with a methanol / acetic acid (9:1 volume ratio) mixture for 24 h to remove the template molecule. It was then washed with methanol until neutral and dried under vacuum at 40 ℃ for 6 h to obtain Fe3O4@PVBC-CPDB / chitosan@MIP magnetic molecularly imprinted aerogel.

[0069] Step 7: Reduction and Regeneration Process Take 0.10 g of the above aerogel and immerse it in 20 mL of 10 mM DTT aqueous solution, then shake at 25 °C for 30 min. After removal, wash it three times with deionized water, and then place it in air for oxidization for 12 h to allow the disulfide bonds to reform, completing one regeneration cycle.

[0070] Example 7 This embodiment provides a method for preparing a magnetically separable and recyclable magnetic molecularly imprinted water purification material, which includes the following steps: Step 1: Preparation of Fe3O4 nanoparticles Same as step 1 in Example 1.

[0071] Step 2: Preparation of Fe3O4@PVBC core-shell particles Same as step 2 in Example 1.

[0072] Step 3: Preparation of Fe3O4@PVBC-CPDB magnetic RAFT reagent Same as step 3 in Example 1.

[0073] Step 4: Preparation of electrospinning solution Same as step 4 in Example 1.

[0074] Step 5: Electrospinning to prepare magnetic nanofiber membranes Same as step 5 in Example 1.

[0075] Step 6: Surface molecular imprinting polymerization Same as step 6 in Example 1.

[0076] Step 7: Reduction and Regeneration Process Take 0.10 g of the above fiber membrane and immerse it in 20 mL of 10 mM DTT aqueous solution, then shake at 25 °C for 30 min. After removal, wash it three times with deionized water, and then place it in air for oxidization for 12 h to allow the disulfide bonds to reform, completing one regeneration cycle.

[0077] Comparative Example 1 This comparative example provides a method for preparing a water purification material, which includes the following steps: Steps 1-5: Same as steps 1-5 in Example 1.

[0078] Step 6: Surface molecular imprinting polymerization (monomers without disulfide bonds) 0.20 g of the magnetic nanofiber membrane prepared in step 5 of Example 1 was immersed in 20 mL of acetonitrile. 0.050 g of bisphenol A (BPA, template molecule), 0.106 g of 4-VP (functional monomer), 0.229 g of EGDMA (crosslinking agent, disulfide-free monomer), and 0.005 g of AIBN were added. Nitrogen gas was purged for 30 min to remove oxygen. The membrane was then sealed and placed in a 60 °C oil bath with magnetic stirring for 12 h. After the reaction, the fiber membrane was removed and Soxhlet extracted with a methanol / acetic acid (9:1 volume ratio) solution for 24 h to remove the template molecule. It was then washed with methanol until neutral and dried under vacuum at 40 °C for 6 h to obtain a Fe3O4@PVBC-CPDB / PAN@MIP magnetic molecularly imprinted nanofiber membrane without disulfide crosslinks.

[0079] Comparative Example 2 This comparative example provides a method for preparing a water purification material, which includes the following steps: Steps 1-3: Same as steps 1-3 in Example 1.

[0080] Step 4: Powder surface molecular imprinting polymerization 0.30 g of Fe3O4@PVBC-CPDB magnetic RAFT reagent was dispersed in 20 mL of acetonitrile and ultrasonically dispersed for 15 min. Then, 0.075 g of bisphenol A (BPA, template molecule), 0.129 g of 4-VP (functional monomer), 0.034 g of bis(2-vinylpyridine) disulfide (3 mol% of total monomers), 0.309 g of EGDMA, and 0.008 g of AIBN were added. The mixture was purged with nitrogen for 30 min to remove oxygen, sealed, and placed in a 60 ℃ oil bath with magnetic stirring for 12 h. After the reaction, the product was magnetically separated and collected. The product was then Soxhlet extracted with a methanol / acetic acid (9:1 v / v) mixture for 24 h to remove the template molecule, washed with methanol until neutral, and vacuum dried at 40 ℃ for 6 h to obtain zero-dimensional powdered Fe3O4@PVBC-CPDB@MIP magnetic molecularly imprinted powder.

[0081] Comparative Example 3 This comparative example provides a method for preparing a water purification material, which includes the following steps: Step 1: Preparation of Fe3O4 nanoparticles Same as step 1 in Example 1.

[0082] Step 2: Preparation of electrospinning solution 0.42 g of the above Fe3O4 nanoparticles (without PVBC-CPDB modification) were dispersed in 10 mL of DMF and ultrasonically dispersed for 20 min. 1.58 g of PAN (Mw=150,000) was added, and the mixture was magnetically stirred in a 60 ℃ water bath for 4 h until completely dissolved to obtain a homogeneous spinning solution.

[0083] Step 3: Electrospinning to prepare Fe3O4 / PAN magnetic nanofiber membranes Following the same procedure as in Example 1, step 5, a Fe3O4 / PAN magnetic nanofiber membrane was obtained.

[0084] Step 4: Surface molecular imprinting polymerization (physical adsorption method) 0.20 g of the above Fe3O4 / PAN magnetic nanofiber membrane was immersed in 20 mL of acetonitrile. 0.108 g of 4-VP, 0.234 g of EGDMA, and 0.235 g of bisphenol A (template molecule to functional monomer molar ratio of 1:4) were added, and the membrane was subjected to ultrasonic-assisted adsorption for 30 min. Subsequently, 0.010 g of AIBN was added, and nitrogen gas was purged for 30 min to remove oxygen. The membrane was then sealed and placed in a 60 ℃ oil bath, and magnetically stirred for 12 h. After the reaction, the fiber membrane was removed and Soxhlet extracted with a methanol / acetic acid (9:1 volume ratio) mixture for 24 h to remove the template molecules. It was then washed with methanol until neutral and vacuum dried at 40 ℃ for 6 h to obtain the physically doped Fe3O4 / PAN@MIP magnetic molecularly imprinted nanofiber membrane.

[0085] Test methods and results: (a) Testing methods 1. Static adsorption capacity test Accurately weigh 20 mg of the material prepared in each example or comparative example, place it in a 50 mL Erlenmeyer flask, and add 20 mL of a 200 mg / L aqueous solution of the target pollutant (Bisphenol A solution was used in Examples 1, 4, 7 and Comparative Examples 1-3; tetracycline solution was used in Examples 2 and 5; and sulfadiazine solution was used in Examples 3 and 6). Place the Erlenmeyer flask in a constant temperature shaker and shake at 25 °C and 150 rpm for 2 h for adsorption. After adsorption, separate the material with a magnet, take the supernatant and filter it through a 0.22 μm filter membrane, and determine the residual concentration using a high-performance liquid chromatograph (HPLC with a UV detector). The adsorption capacity Q (mg / g) is calculated using the following formula: Q = (C0 - C e ) × V / m Where C0 is the initial concentration (mg / L), C e The adsorption equilibrium concentration is V (mg / L), V is the solution volume (L), and m is the material mass (g).

[0086] 2. Magnetic Separation Time Test Accurately weigh 20 mg of the material prepared in each example or comparative example, disperse it in 20 mL of deionized water, and sonicate for 30 s. Place the glass bottle containing the dispersion on one side of a neodymium iron boron permanent magnet (surface magnetic field strength 0.3 T), and record the time from the placement of the magnet to the complete clarification of the solution, which is the magnetic separation time. Each test is repeated 3 times, and the average value is taken.

[0087] 3. Cyclic Regeneration Performance Test Cyclic regeneration tests were conducted using Examples 1, 4, 7, and Comparative Examples 1-3 as examples. 20 mg of material was taken and subjected to initial adsorption according to the static adsorption capacity test method described above. After adsorption, magnetic separation was performed, and the material was treated according to the regeneration methods of each example or comparative example (Examples 1-7 were treated under the reduction and regeneration conditions of step 7; Comparative Example 1 was washed three times with a methanol / acetic acid (9:1 volume ratio) solution for 30 min each time; Comparative Example 2 was regenerated by treatment with 10 mM DTT for 30 min as described in Example 7; Comparative Example 3 was washed three times with a methanol / acetic acid (9:1 volume ratio) solution for 30 min each time). The regenerated material was then subjected to adsorption tests again, and the above adsorption-regeneration cycle was repeated 30 times. The adsorption capacity was recorded each time, and the adsorption capacity retention rate after the 30th cycle was calculated as (30th adsorption capacity / initial adsorption capacity × 100%).

[0088] 4. Material Loss Rate Test Accurately weigh 50 mg of the material prepared in each example or comparative example, place it in 100 mL of deionized water, and stir at 500 rpm for 30 min on a magnetic stirrer. Then perform magnetic separation, collect the supernatant, filter it through a 0.22 μm filter membrane, and dry the solid residue on the filter membrane at 60 °C to constant weight, then weigh it. Material loss rate (%) = (mass of solid residue / initial material mass) × 100%.

[0089] The test results are summarized in Table 1 below: Table 1 sample Adsorption capacity (mg / g) Magnetic separation time (s) Adsorption capacity retention rate (%) after 30 cycles Material loss rate (%) Example 1 138 25 87 1.2 Example 2 142 22 86 1.1 Example 3 145 28 88 0.9 Example 4 132 26 84 1.4 Example 5 148 23 89 1.0 Example 6 143 29 91 0.8 Example 7 136 27 90 1.3 Comparative Example 1 125 24 58 1.3 Comparative Example 2 82 45 72 4.8 Comparative Example 3 96 31 51 5.2 As can be seen from the test results in Table 1 above, the embodiments of the present invention show significant advantages in all performance indicators.

[0090] Regarding adsorption capacity, all embodiments exhibited adsorption capacities exceeding 130 mg / g, with Example 5 reaching 148 mg / g, compared to only 82 mg / g for Comparative Example 2 (zero-dimensional powder morphology) and 96 mg / g for Comparative Example 3 (physical doping method). This indicates that the fibrous membrane or aerogel morphology used in this invention provides a larger specific surface area, increasing the number of effective recognition sites and thus significantly improving adsorption capacity. Although Comparative Example 1 used the same fibrous membrane morphology, its adsorption capacity (125 mg / g) was slightly lower than the embodiments due to the lack of a reversible disulfide crosslinking structure, suggesting that the disulfide crosslinking structure helps optimize the formation quality of imprinted vacancies.

[0091] Regarding magnetic separation time, the magnetic separation time of all embodiments was within 30 s, with the fastest reaching 22 s (Example 2), while Comparative Example 2 (zero-dimensional powder morphology) required 45 s, and some particles were difficult to separate completely. This indicates that the design of dispersing magnetic nanoparticles in a porous matrix in this invention avoids the impact of powder particle agglomeration on magnetic separation efficiency, achieving rapid and thorough magnetic separation.

[0092] Regarding the regeneration performance, the embodiments of the present invention maintained an adsorption capacity retention rate of no less than 84% after 30 adsorption-regeneration cycles, with Example 6 reaching as high as 91%. Comparative Example 1 (without disulfide bond crosslinking) only maintained a retention rate of 58% after 30 cycles. This is because the traditional irreversible crosslinked imprinted network gradually deteriorates during repeated elution, causing irreversible deformation of the imprinted cavities. Comparative Example 2 (zero-dimensional powder + disulfide bonds) maintained a retention rate of 72%, which, while better than Comparative Example 1, was still lower than all other examples. This indicates a synergistic effect between reversible disulfide bond crosslinking and the porous matrix morphology—the porous structure facilitates the uniform penetration of reducing agents and oxidizing agents, resulting in more complete breakage and reconstruction of disulfide bonds. Comparative Example 3 (physical doping method) had the lowest retention rate (51%). This is because the molecularly imprinted polymer (MIP) shell and the fiber membrane rely solely on physical adsorption, leading to significant shedding during repeated regeneration.

[0093] Regarding material loss rate, the loss rate of all embodiments was less than 1.5%, with Example 6 at only 0.8%, while Comparative Example 2 had a loss rate of 4.8%, and Comparative Example 3 was even higher at 5.2%. This indicates that the present invention fixes the MIP shell to the surface of the porous substrate through chemical bonding, effectively preventing the detachment of the imprinted layer and the loss of magnetic particles, thus ensuring the structural stability of the material.

[0094] In summary, this invention achieves simultaneous improvement in adsorption capacity, magnetic separation efficiency, cycle stability, and structural stability by organically combining one-dimensional fiber membranes or two-dimensional aerogel morphology, distributed magnetic nanoparticles, and a molecularly imprinted polymer shell with reversible cross-linking of disulfide bonds. Its overall performance is significantly superior to existing technical solutions.

Claims

1. A magnetically separable and recyclable magnetic molecularly imprinted water purification material, characterized in that, Including porous matrices in the form of one-dimensional fibrous or two-dimensional aerogel; Magnetic nanoparticles are dispersed in the porous matrix; The porous matrix has a molecularly imprinted polymer shell with a reversible cross-linked structure containing disulfide bonds bonded to its surface. The molecularly imprinted polymer shell can break disulfide bonds under the action of a reducing agent, thereby releasing the identified template molecule, and reforming disulfide bonds under oxidative conditions to restore the molecularly imprinted hole.

2. The magnetic molecularly imprinted water purification material according to claim 1, characterized in that, The porous substrate is a one-dimensional electrospun fiber membrane with a thickness of 50–200 μm, a fiber diameter of 200–500 nm, and a porosity of 70%–85%.

3. The magnetic molecularly imprinted water purification material according to claim 1, characterized in that, The porous matrix is ​​a two-dimensional magnetic aerogel formed by freeze-drying, with a porosity greater than 90% and a density of 0.02–0.05 g / cm³. 3 .

4. The magnetic molecularly imprinted water purification material according to any one of claims 1 to 3, characterized in that, The magnetic nanoparticles have an Fe3O4@PVBC core-shell structure, and the PVBC shell is connected to the RAFT chain transfer agent CPDB.

5. The magnetic molecularly imprinted water purification material according to any one of claims 1 to 3, characterized in that, The molecularly imprinted polymer shell is formed by polymerizing a polymerization system containing disulfide-bonded monomers, functional monomers, and crosslinking agents in the presence of template molecules.

6. The magnetic molecularly imprinted water purification material according to claim 5, characterized in that, The disulfide-containing monomer is a bis(2-vinylpyridine) disulfide, which accounts for 3 mol% to 8 mol% of the total monomer.

7. The magnetic molecularly imprinted water purification material according to claim 1, characterized in that, The reducing agent is dithiothreitol, with a concentration of 5–20 mM, and the treatment time is 20–40 min.

8. A method for preparing the magnetic molecularly imprinted water purification material according to any one of claims 1 to 7, characterized in that, Includes the following steps: (1) Preparation of a porous matrix containing magnetic nanoparticles; (2) Molecular imprinting polymerization is carried out on the surface of the porous matrix, wherein the polymerization system contains reversible crosslinking monomers containing disulfide bonds to form a molecular imprinted polymer shell containing a reversible crosslinking structure of disulfide bonds. (3) Wash away the template molecules to obtain the magnetic molecularly imprinted water purification material.

9. The method according to claim 8, characterized in that, The porous matrix described in step (1) is obtained by electrospinning or freeze-drying. When electrospinning is used, magnetic nanoparticles are dispersed in the spinning solution and spun into a film. When freeze-drying is used, magnetic nanoparticles are mixed with chitosan solution and then freeze-dried to form an aerogel; The molecular imprinting polymerization described in step (2) adopts surface-initiated RAFT polymerization, using CPDB on the surface of magnetic nanoparticles as a chain transfer agent.

10. A method for purifying water using the magnetic molecularly imprinted water purification material according to any one of claims 1 to 7, characterized in that, The material is added to water containing organic pollutants. After the pollutants are adsorbed, the material is separated and recovered by an external magnetic field. Then, a reducing agent is used to break the disulfide bonds in the molecularly imprinted polymer shell, releasing the pollutants. The disulfide bonds are then rebuilt through oxidation, thus achieving the recycling of the material.